Competition can harm consumers - Cowan, S; Yin, X (2006)
Duopolists selling differentiated products can generate less consumer surplus than a monopoly selling one of the products. In a Hotelling model where a monopoly supplies more than half of potential consumers, but not all, entry by a rival leads to a duopoly price that is higher than the monopoly price. Consumers in aggregate will be made worse off by such entry when the effect of the price increase outweighs the benefit of extra variety. When consumers have continuous demand functions and firms use two-part tariffs, duopoly can also result in lower aggregate consumer surplus than monopoly.